2021
DOI: 10.18235/0003315
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Mobility during the COVID-19 Pandemic: An Analysis of Eight Large Latin American Cities

Abstract: This study analyzes mobility patterns during the COVID-19 pandemic for eight large Latin American cities. Indicators of mobility by socioeconomic status (SES) are generated by combining georeferenced mobile phone information with granular census data. Before the pandemic, a strong positive association between SES and mobility is documented. With the arrival of the pandemic, in most cases, a negative association between mobility and SES emerges. This new pattern is explained by a notably stronger reduction in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Of course, the interpretation of these factors is not as intuitive as mobility and we certainly do not wish to attribute direct causality to them. However, there are a variety of relevant factors for COVID-19 that can be related to internet access and computer usage for example, such as age, educational status, population density [21], as urban areas have better infrastructure, and mobility itself [22, 23]. As with any epidemiological or ecological model, the interpretation of the predictors as representing direct versus indirect interactions is highly non-trivial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the interpretation of these factors is not as intuitive as mobility and we certainly do not wish to attribute direct causality to them. However, there are a variety of relevant factors for COVID-19 that can be related to internet access and computer usage for example, such as age, educational status, population density [21], as urban areas have better infrastructure, and mobility itself [22, 23]. As with any epidemiological or ecological model, the interpretation of the predictors as representing direct versus indirect interactions is highly non-trivial.…”
Section: Discussionmentioning
confidence: 99%
“…) and P (C | X n j = 1) for each value of the habitat variable ranges X m i =Average annual temperature and X n j =Internal labor flow of the municipality corresponding to a "climate-only" model and a "mobility-only" model. related to internet access and computer usage for example, such as age, educational status, population density [21], as urban areas have better infrastructure, and mobility itself [22,23]. As with any epidemiological or ecological model, the interpretation of the predictors as representing direct versus indirect interactions is highly non-trivial.…”
Section: Discussionmentioning
confidence: 99%
“…A strand of the literature has shown evidence for unequal mobility changes across demographic and socioeconomic groups amid COVID-19, which may be effective on the spread of COVID-19. Among others Aromí et al. (2020), have shown that higher socioeconomic status is associated with more intense reductions in mobility based on data from 8 large Latin American urban areas.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, given the information we have available, it is not possible to identify these characteristics for each user, and, therefore, we cannot estimate the heterogeneous effects of lockdowns for different groups. Still, a recent paper by Aromí et al (2021) shed light on this issue. The study explored the differential change in mobility by socioeconomic status for eight large Latin American cities during the beginning of the pandemic.…”
Section: Dynamic Impacts Of Lockdowns Per Countrymentioning
confidence: 99%